2001
DOI: 10.1103/physrevb.64.195410
|View full text |Cite
|
Sign up to set email alerts
|

Collective excitations in alkali metals on Al(111)

Abstract: The photon-excited multipole plasmon and the bulklike plasmon modes have been studied in Na/Al͑111͒ and K/Al͑111͒. These collective modes appear for a coverage of у2 monolayers. Both the multipole and the bulklike plasmon modes exhibit interesting variations in frequency, line shape, and relative intensity with adlayer coverage. The reasons for such behavior are discussed on the basis of existing theoretical results. The substrate Al multipole plasmon is found to be attenuated by smooth adlayer growth. Deposit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
27
0

Year Published

2004
2004
2013
2013

Publication Types

Select...
8

Relationship

4
4

Authors

Journals

citations
Cited by 18 publications
(30 citation statements)
references
References 51 publications
(99 reference statements)
3
27
0
Order By: Relevance
“…The substrate is held at 130 K to avoid possible surface alloying that is ob-served for alkali metals at room temperature. 18 During deposition, the chamber pressure rose to 9 ϫ 10 −11 mbar. The thickness of the adlayers has been calculated from the area under the ͑Na 1s and K 2p͒ and ͑Al 2p͒ core-level peaks, as in our previous work.…”
Section: Methodsmentioning
confidence: 99%
“…The substrate is held at 130 K to avoid possible surface alloying that is ob-served for alkali metals at room temperature. 18 During deposition, the chamber pressure rose to 9 ϫ 10 −11 mbar. The thickness of the adlayers has been calculated from the area under the ͑Na 1s and K 2p͒ and ͑Al 2p͒ core-level peaks, as in our previous work.…”
Section: Methodsmentioning
confidence: 99%
“…3,6,7 The advantage of AERPY over total yield measurement is that it does not have contributions from inelastically scattered secondary electrons, which are difficult to analyze and may also depend on surface quality and sample preparation history. 7 The data were recorded in the normal emission geometry using p-polarized light incident at 45°to the surface normal. The angular resolution of the analyzer was 3°.…”
Section: Methodsmentioning
confidence: 99%
“…Theoretical work on the surface response of metals has been performed extensively, and there is reasonable agreement between the theory and experiment for free-electron-like metals. [1][2][3][4][5][6][7] However, in metals such as Ag, the optical properties of which have also been studied extensively, this agreement has not been reached; here the influence of occupied 4d bands on the surface collective excitations results in a remarkably different behavior compared to the free-electron-like metals. For example, the energies of the Ag bulk plasmon p and monopole surface plasmon s are drastically reduced due to the presence of the filled Ag 4d bands.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…1,2 Quantum well states and collective excitation in alkali metal adlayers on metals have been extensively studied. [3][4][5] Icosahedral Al-Pd-Mn ͑i-Al-Pd-Mn͒ is a complex ternary alloy quasicrystal exhibiting unusual properties such as high resistivity, high frictional constant, and a low sticking coefficient. 6,7 Scanning tunneling microscopy ͑STM͒ experiments have shown that the surface corrugation of quasicrystalline surfaces is quite different from that of metals.…”
Section: Introductionmentioning
confidence: 99%